Fear and Uncertainty: The Surrogacy Triad's Experience of Social Workers' Role Ambiguity. (7th September 2020) - Walker, Ruth; van Zyl, Liezl
Abstract: In New Zealand, as in the UK, the surrogate is the legal mother of the child until parentage is transferred by the court to the intended parents. Social workers are responsible for assessing the intended parents' suitability to parent and scrutinising the arrangement. However, courts almost invariably transfer parentage, regardless of their recommendations, with the result that social workers experience a significant amount of role ambiguity. We conducted semi-structured interviews with surrogates and intended parents about their experience of surrogacy in New Zealand, focussing on the changes they would like to see in the regulatory framework, particularly with regards to legal parentage and the involvement of social workers in assessing intending parents' suitability to parent. Thematic analysis of interview transcripts showed that role ambiguity and role conflict experienced by social workers have their corollary in the experience of intended parents and surrogates, where it manifests as either fear that the adoption could be declined or uncertainty about the purpose of the social worker's involvement. Although participants recommended that their role be eliminated—along with the adoption process itself—we argue that there is a valuable role for social workers at the beginning of the process.